Development of Guided Inquiry Lesson Based on Ethnoscience E-Modules to Improve Students’ Problem-solving Ability in Chemistry Class - Syahmani Syahmani; Jahidah Rahmatilah; Atiek Winarti; Muhammad Kusasi; Rilia Iriani; Yogo Dwi Prasetyo (Journal of Innovation in Educational and Cultural Research, 2022)
The limitations of teaching materials in the implementation of distance learning coupled with students’ low problem-solving ability led to the need to develop teaching materials in the form of guided inquiry to improve students’ ability to solve problems. This development research aims to determine the validity, practicality, and effectiveness of the Guided Inquiry Lesson Based on Ethnoscience (GILBE) e-module. This development research employs the Research and Development (RD) approach with a 4D development model, meaning define, design, develop, and disseminate. GILBE e-module on colloid material was piloted on 16 students SMA at Central Kalimantan in the limited trial and 30 students SMA at South Kalimantan in the broad trial. The validity test was measured using a validation sheet. The practicality test was measured using a readability questionnaire, student and teacher responses, and the effectiveness test was measured using a problem-solving ability test instrument in the form of ten essay questions. Descriptive and inferential statistical analysis was used to analyze the data. The findings revealed that the designed e-module matched valid, practical, and effective. The effectiveness is based on the p-value 0.05 in the limited and broad trial of the N-gain of students’ problem-solving abilities in the high category and can be used in the chemistry learning process. Further research will develop teaching materials for higher-order thinking that apply the GILBE model, which is of higher quality.